Sleep-wake patterns and sleep quality in urban Georgia - Sakhelashvili Irine (De Gruyter, 2016)
Sleep problems represent a worldwide health concern but their prevalence and impacts are unknown in most non-European/North American countries. This study aimed to evaluate sleep-wake patterns, sleep quality and potential correlates of poor sleep in a sample of the urban Georgian population.